A Plethora of Fungi: Teaching a Middle School Unit on Fungi. (3rd April 2019) - Green, Kathryn; Roller, Christine; Cubeta, Marc
Abstract: While fungi play a vital role in Earth's ecosystems, they are not highlighted in the Next Generation Science Standards (NGSS). This article contains a unit plan to introduce students to the fungal kingdom, characteristics of fungi, and their role as decomposers. The unit plan is written in a 5E model format and can be adjusted for any type of lesson planning format. Students explore fungi through hands-on activities, a jigsaw activity that makes use of collaborative learning, and analysis of case studies. Teachers can use this unit without a strong background in mycology, the study of fungi, or costly materials. A summative assessment is included at the end of the unit plan.